Air promoted annulation of thiophenols with alkynes leading to benzothiophenes. Issue 10 (15th February 2018) - Wang, Yajun; Wu, Rui; Zhao, Shijun; Quan, Zhengjun; Su, Yingpeng; Huo, Congde
Abstract : Air promoted intermolecular annulation of thiophenols with alkynes, leading to complex benzothiophenes, is reported. Abstract : Air promoted intermolecular annulation of thiophenols with alkynes, leading to complex benzothiophenes, is reported. This atom-economical reaction is performed in the absence of any catalyst, chemical oxidant and additive. Only a solvent and an air atmosphere were required. A plausible radical involved mechanism is proposed.